PAINTING WITH WORDS: A COMPARATIVE STUDY OF AJINIYAZ AND BYRON’S IMAGERY - Khadjieva, D.T.; Erimbetova, E.K. (SCIENCE and SOCIETY, 2024)
This article discusses analysis that Byron and Ajiniyaz both use imagery as a powerful tool to convey personal, cultural, and political ideas, yet their methods and intentions differ significantly. Ajiniyaz’s focus on collective identity and resilience, with his imagery rooted in the cultural and historical experiences of the Karakalpak people. Both poets, however, succeed in transforming imagery into a bridge between the emotional and the universal, making their works resonate across time and place.